1996
DOI: 10.1046/j.1365-3059.1996.d01-10.x
|View full text |Cite
|
Sign up to set email alerts
|

The biology and pathology of the fungus Rhizopusstolonifer, cause of black mould disease of table grapes in Israel

Abstract: Rhizopus stolonifer causes severe losses to Israeli grape exports. The fungus develops on mature berries in the field, during storage at temperatures above 08C and during shelf‐life. It was isolated from naturally contaminated soils throughout the year, and from fruits after mid‐June. The airborne spore population increased in vineyards at the time of fruit maturation and was related to the proximity of stone‐fruit orchards. The size of this population was highly correlated with disease incidence and thus may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 2 publications
3
9
0
4
Order By: Relevance
“…This may be explained by the fact that T. harzianum is a strictly wound -parasite, so it can penetrate host tissues only through bruises and fresh wounds, especially in the fields through harvesting, handling, insects, and rodents (Barnes, 1979;Lisker et al, 1996). A similar significant effect was obtained in a previous study in controlling P. expansum on unwounded apple fruits (Batta, 2004) when these fruits were dipped for 30 in formulated T. harzianum conidia before being inoculated by P. expansum compared to the wounded fruits.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the fact that T. harzianum is a strictly wound -parasite, so it can penetrate host tissues only through bruises and fresh wounds, especially in the fields through harvesting, handling, insects, and rodents (Barnes, 1979;Lisker et al, 1996). A similar significant effect was obtained in a previous study in controlling P. expansum on unwounded apple fruits (Batta, 2004) when these fruits were dipped for 30 in formulated T. harzianum conidia before being inoculated by P. expansum compared to the wounded fruits.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizopus stolonifer infection has already been reported for several hosts. The infection on grapes can occur due to the release of cellular substances caused by injuries to berry pedicels or incomplete connections between berry and pedicel (Lisker et al, 1996;Tavares & Silva, 2006). Furthermore, it was found that the removal of the raspberry receptacle during harvest resulted in a cavity, which released substances that promoted a favourable humidity and nutrient supply for Rhizopus development (Davis, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, dark sporulation forms a mass of black sporangia at their tips, covering the entire surface of the commodity. Lisker et al (1996) reported that germinating Rhizopus spores in inoculated grapes were observed after 12-15 h; one h later, germ tubes started to develop and, after 24 h, fruit was covered by hyphae. For tomatoes, no germination took place by 5 h (Fig.…”
Section: Biology Of the R Stolonifer Infection Processmentioning
confidence: 99%
“…For the control of this fungus, calcium and sodium hypochlorite have also been tested on table grapes cv. 'Shami' and tomatoes 'V 2 type', respectively (Abdell-Mallek et al 1995;Lisker et al, 1996), resulting in an average efficiency of 100% on table grapes and 47% on tomatoes. Scientific research has proved that ozone (O 3 ) is another method for controlling decay caused by R. stolonifer.…”
Section: Sanitizersmentioning
confidence: 99%